Traffic Accident Risk Among Intercity Bus Drivers: Evidence from Eldivo Bus Services in Pematang Siantar - Yusuf Syahputra Siregar; Susilawati (Karya Kesehatan Siwalima, 2026)
Traffic accidents remain a significant issue in the transportation sector, particularly in public transport modes such as intercity buses. This study aimed to analyze accident risk among Eldivo intercity bus drivers in Pematang Siantar based on three key variables: driver knowledge, driving compliance, and vehicle roadworthiness. This study employed a quantitative approach with a descriptive-analytical design. The sample consisted of 60 drivers selected using a total sampling technique. Data were collected through structured questionnaires and observations and analyzed using univariate, bivariate (chi-square test), and multivariate (logistic regression) analyses. The univariate analysis showed that 45% of drivers had experienced traffic accidents. The bivariate analysis indicated that poor knowledge, low driving compliance, and unroadworthy vehicles were significantly associated with accident risk (p < 0.05). The multivariate logistic regression analysis revealed that poor knowledge increased accident risk by 14.205 times (p = 0.005), low driving compliance by 16.987 times (p = 0.002), and unroadworthy vehicles by 15.964 times (p = 0.012). The regression model also yielded a Nagelkerke R² value of 0.651, indicating that 65.1% of the variance in accident risk could be explained simultaneously by these three variables. In conclusion, driver knowledge, driving compliance, and vehicle roadworthiness significantly influence accident risk. Therefore, efforts to improve safety should include regular training programs for drivers, strengthened monitoring of driving compliance, and periodic technical vehicle inspections.